1998
DOI: 10.1105/tpc.10.5.721
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Secondary Metabolism in Maize Cells by Ectopic Expression of Transcription Factors

Abstract: Manipulation of plant natural product biosynthesis through genetic engineering is an attractive but technically challenging goal. Here, we demonstrate that different secondary metabolites can be produced in cultured maize cells by ectopic expression of the appropriate regulatory genes. Cell lines engineered to express the maize transcriptional activators C1 and R accumulate two cyanidin derivatives, which are similar to the predominant anthocyanin found in differentiated plant tissues. In contrast, cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(87 citation statements)
references
References 72 publications
6
81
0
Order By: Relevance
“…A MYB-bHLH-WD40 complex consisting of subgroup 5 MYB ZmC1 or ZmPL1, subgroup 3F bHLH ZmR or ZmB, and the WD40 protein ZmPAC1 activates early biosynthetic genes that are shared by all of the flavonoid pathways (e.g., CHS, chalcone isomerase [CHI], flavanone 3-hydroxylase [F3H] and dihydroflavonol 4-reductase [DFR] genes) as well as genes that are specific for the anthocyanin pathway (e.g., anthocyanidin synthase [ANS] and UDP-glucose flavonoid 3- O -glucosyltransferase [UFGT] genes) (Figure 3; Goff et al, 1990; Roth et al, 1991; Tuerck and Fromm, 1994; Grotewold et al, 1998; Selinger and Chandler, 1999; Walker et al, 1999; Carey 2004). By contrast, the subgroup 7 MYB ZmP1 activates the production of the floral organ-specific 3-deoxyflavonoids, independently of any bHLH and WD40 cofactors (Grotewold et al, 1994).…”
Section: Metabolic Pathway Regulationmentioning
confidence: 99%
“…A MYB-bHLH-WD40 complex consisting of subgroup 5 MYB ZmC1 or ZmPL1, subgroup 3F bHLH ZmR or ZmB, and the WD40 protein ZmPAC1 activates early biosynthetic genes that are shared by all of the flavonoid pathways (e.g., CHS, chalcone isomerase [CHI], flavanone 3-hydroxylase [F3H] and dihydroflavonol 4-reductase [DFR] genes) as well as genes that are specific for the anthocyanin pathway (e.g., anthocyanidin synthase [ANS] and UDP-glucose flavonoid 3- O -glucosyltransferase [UFGT] genes) (Figure 3; Goff et al, 1990; Roth et al, 1991; Tuerck and Fromm, 1994; Grotewold et al, 1998; Selinger and Chandler, 1999; Walker et al, 1999; Carey 2004). By contrast, the subgroup 7 MYB ZmP1 activates the production of the floral organ-specific 3-deoxyflavonoids, independently of any bHLH and WD40 cofactors (Grotewold et al, 1994).…”
Section: Metabolic Pathway Regulationmentioning
confidence: 99%
“…Vesicles involved in the transport of flavonoid-derived compounds have been found in maize and in sorghum cells (Snyder and Nicholson, 1990; Grotewold et al, 1998; Grotewold and Davies, 2008; Figure 2 , transporter 12). It could be further demonstrated that anthocyanins are transported to the cell wall or the vacuole by at least two distinct vesicle trafficking pathways (Lin et al, 2003).…”
Section: Transport Mediated By Vesicle Trafficking In Plant Cellsmentioning
confidence: 99%
“…The much studied Pericarp1 ( P1 ) is an R2R3-MYB transcription factor which can control the accumulation of various phenylpropanoids by activating a subset of flavonoid biosynthetic genes [33, 34]. The C1 like R2R3-MYB and R1 like bHLH interacting factors also activate the pathway [35].…”
Section: Introductionmentioning
confidence: 99%